Delayed Initiation of Antenatal Care among Pregnant Women in Indonesia: Findings from a Multi-Centered Cross-Sectional Study - Wiqodatul Ummah; Yanti Rosdiana; Woro Tri Utami (Universitas STRADA Indonesia, 2026)
Background: Early initiation of antenatal care (ANC) is critical for optimizing maternal and neonatal health outcomes, yet late initiation remains a persistent challenge in many low- and middle-income countries. Purpose: This study aimed to investigate the magnitude and factors associated with delayed initiation of antenatal care among pregnant women in Indonesia in Malang City and Malang Regency, Indonesia. Methods: A facility-based cross-sectional study was conducted from May to July 2025 among 309 pregnant women selected using systematic random sampling from one hospital and two health centers. Delayed ANC initiation was defined as the first ANC visit after 12 completed weeks of gestation. Data were collected using a structured interviewer-administered questionnaire and medical record review, then analyzed using bivariable and multivariable logistic regression. Results: The prevalence of delayed ANC initiation was 57.3% (95% CI: 51.7-62.9), indicating suboptimal utilization of maternal health services. Multivariable analysis revealed that low maternal education (AOR = 2.31; 95% CI: 1.42-3.76), unplanned pregnancy (AOR = 1.89; 95% CI: 1.12-3.19), lack of advice from health professionals (AOR = 2.67; 95% CI: 1.58-4.51), poor knowledge (AOR = 2.45; 95% CI: 1.51-3.98), longer distance to health facilities (AOR = 2.12; 95% CI: 1.18-3.81), and cultural beliefs discouraging early pregnancy disclosure (AOR = 1.87; 95% CI: 1.12-3.12) were significantly associated with delayed initiation. Conclusion: Delayed ANC initiation is influenced by multiple socio-demographic, cognitive, behavioral, health system, and cultural factors. These findings highlight the need for policies that strengthen early pregnancy counseling, improve maternal health literacy, and enhance timely ANC initiation in Indonesia.